Learning with Lenin : selected works on education and revolution - Lenin, Vladimir Illyich, 1870-1924 (Marxist, socialist, and communist studies in education, 2019)
"Learning with Lenin brings together, for the first time, Lenin's classic texts and his speeches and writings on education. To facilitate educators and activists' engagement with these works, a study and discussion guide accompanies each text. Learning with Lenin contributes to the rematerialization of a revolutionary movement in the U.S. by focusing on the pedagogy of Lenin. After a series of setbacks and attacks that seriously degraded its status in both working-class struggles and educational theory, socialism is once again on the rise. Like the generations before them, organizers, activists, and educators are once again turning to classic works of socialism to understand and respond to the systematic depravities of imperialism, white supremacy, and settler-colonialism. Learning with Lenin will assist anyone interested in reading and applying Lenin's theories to our current era, with all of its complexities and contradictions"--